Pengaruh Pemasaran Konten dan Konten Buatan Pengguna Terhadap Keputusan Pembelian di Kedai Kopi Potatoes Project Gorontalo - Zahra Amidu; Tineke Wolok; Valentina Monoarfa (Transbahasa, 2026)
The rapid growth of the coffee industry in Gorontalo creates fierce competition that demands an effective digital marketing strategy to maintain the stability of consumer visits. This study aims to determine the influence of Content Marketing partially on consumer purchase decisions, the influence of User Generated Content partially on consumer purchase decisions, and the simultaneous influence of Content Marketing and User Generated Content on consumer purchase decisions in Coffee Shops Potatoes Project Gorontalo. The research uses a quantitative method with an associative research type. The sample was determined through a purposive sampling technique using the Lemeshow formula so that 100 respondents were obtained. Data analysis was carried out using SPSS (Statistical Product and Service Solutions) version 22 with multiple linear regression analysis techniques. The results of the study show that Content Marketing has a positive and significant effect on consumer purchase decisions with a t-count value of 5,330 which is greater than the t-table of 1,984. User Generated Content partially had no significant effect on consumer purchase decisions with a t-count value of 1.937 which was smaller than the t-table of 1.984. Simultaneously, Content Marketing and User Generated Content had a positive and significant effect on consumer purchase decisions with an f-calculation value of 36.633 which was greater than the f-table value of 3.09. The magnitude of the influence of the two variables on purchasing decisions was 65.6%, while 34.4% was influenced by other factors outside the study.